Fluoro boric acid composite coated sodium ion battery layered positive electrode material and preparation method thereof
Through the fluoroboric acid composite coating technology, the surface of the layered positive electrode material of sodium ion battery is compositely coated with fluoride and borate, which solves the problem that the material is easy to react with air and significantly improves the air stability and electrochemical properties of the material.
Patent Information
- Application Number
- CN202411753440.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-02
- Publication Date
- 2025-04-25
AI Technical Summary
The existing sodium ion battery positive electrode materials are prone to react with water and carbon dioxide in the air, resulting in crystal structure damage and capacity attenuation. The quality of the oxide coating agent is insufficient, making it difficult to completely coat the material, reducing the air stability of the material and the quality of the active material that can provide capacity.
The surface of the layered positive electrode material of sodium ion battery is coated with fluoride and borate by chemical reaction, and the surface residual alkali is removed to form an active coating of sodium fluoroborate, which improves the air stability and electrochemical properties of the material.
It significantly improves the air stability and electrochemical properties of the material, extends the cycle life of the material, reduces voltage decay, and improves the magnification characteristics.
Smart Images

Figure CN119890284A_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the technical field of energy materials, and in particular relates to a sodium ion battery layered positive electrode material coated with fluoroboric acid composite and a preparation method thereof. Background Art
[0002] Among the positive electrode materials for sodium-ion batteries, the technical production routes of layered oxides are similar to those of layered oxide materials for positive electrodes of lithium-ion batteries, and the preparation and technical transformation are easy. At present, the fastest commercialized sodium positive electrode is mainly layered oxides. Although layered oxides are simple to prepare, this type of material easily reacts with water and carbon dioxide in the air to form sodium carbonate microcrystals, which destroys the crystal structure and causes capacity decay. Currently, oxide coating is mostly used to improve this problem. The oxide coating agent generally only accounts for 1-5% of the material mass percentage. Therefore, after oxide coating, it is difficult to completely coat the material, and the capacity will be reduced. Although increasing the mass percentage of the oxide coating agent can increase the degree of coating of the material, reduce the contact area between the material and the air, and further improve the air stability of the material, it will also reduce the mass ratio of the active material that can provide capacity, and the specific capacity will be further reduced. Summary of the invention
[0003] The present application provides a sodium ion battery layered positive electrode material coated with fluoroboric acid composite and a preparation method thereof, aiming to solve the problem of difficulty in achieving both coating degree and specific capacity to a certain extent.
[0004] In the first aspect, a sodium ion battery layered positive electrode material coated with fluoroboric acid has the general formula of Na x TMO2, wherein 0.44≤x≤1.0, the surface of the sodium ion battery layered positive electrode material has a composite coating layer of fluoride and borate, and the surface of the primary particles constituting the sodium ion battery layered positive electrode material has an inorganic coating layer.
[0005] In some embodiments, the TM is one or a combination of transition metal ions Ti, Mg, Co, Cu, Al, Zn, Li, Ni, Fe, Mn and Zr; and the thickness of the composite coating layer is 5-10 nm.
[0006] Based on the fact that there is a large amount of residual inert sodium carbonate / sodium bicarbonate / sodium hydroxide mixture on the surface of the sodium electric layer oxygen positive electrode, the present invention uses fluoride and borate as a composite coating layer, and uses fluoroborate to undergo a chemical reaction to remove the surface inert sodium carbonate / sodium bicarbonate / sodium hydroxide mixture and other substances, while forming an active coating layer of sodium fluoroborate, which can reduce the residual alkali on the surface of the material, improve the subsequent processing performance of the material, and improve the safety performance of the sodium battery cell. At the same time, the electrochemical performance of the material is improved. The main chemical equation is as follows:
[0007] H4BF4N reacts with Na2CO3: H4BF4N+Na2CO3=NaBF4+NaHCO3+NH3,
[0008] H4BF4N reacts with NaHCO3: H4BF4N+NaHCO3=NaBF4+CO2+NH3·H2O,
[0009] H4BF4N reacts with NaOH: H4BF4N+NaOH=NaBF4+NH3·H2O.
[0010] By selecting solvents and surfactants and controlling low temperature, an ultra-thin fluoroborate coating layer is obtained. At the same time, the layered oxide cathode substrate material is not damaged, and a fine controllable chemical reaction is performed to turn the waste on the cathode surface into an active ultra-thin coating layer. The coating treatment time of the layered cathode material of the sodium ion battery is adjusted by the ratio of solvent to water. The properties of the solvent, such as polarity, viscosity, dielectric constant, etc., will affect the rate of the chemical reaction. By adjusting the ratio of solvent to water, these properties of the solvent can be changed, thereby affecting the rate of the coating reaction. Surfactants play multiple roles in the aqueous phase coating of the cathode material of the sodium ion battery, including improving wettability, stabilizing the structure, and promoting charge transfer. These effects together improve the performance and stability of the battery.
[0011] The solution of the present application can realize the complementary advantages of the two technologies of material surface coating and bulk doping, and can endow the positive electrode material with stable cycle life, weak voltage decay, outstanding rate characteristics and other superior comprehensive electrochemical properties by uniformly doping the surface of the layered positive electrode material of the sodium ion battery.
[0012] In a second aspect, the present application provides a method for preparing a sodium ion battery layered positive electrode material coated with fluoroboric acid as described in the first aspect, comprising the following steps:
[0013] S1, preparing a mixed solvent of water and a polar organic solvent, adding fluoroborate and a surfactant, and mixing them uniformly to obtain a first solution;
[0014] S2, adding a sodium ion battery layered cathode material to the first solution and stirring to obtain a second suspension;
[0015] S3, stirring the second suspension, centrifuging and drying to obtain a first sodium ion battery layered positive electrode material with fluoroborate uniformly attached to the surface;
[0016] S4, calcining the first sodium ion battery layered positive electrode material to obtain the sodium ion battery layered positive electrode material coated with fluoroboric acid.
[0017] In some embodiments, in the mixed solvent in S1, the volume ratio of water is greater than or equal to 50%, and the polar organic solvent is a combination of one or more of ethanol, methanol, ethylene glycol, glycerol or DMF.
[0018] In some embodiments, the fluoroborate in S1 is a combination of one or more of sodium fluoroborate, ammonium fluoroborate, stannous fluoroborate or lithium fluoroborate, and the amount of the fluoroborate added is 0.5%-5% of the mass of the mixed solvent.
[0019] In some embodiments, the surfactant in S1 is a combination of one or more of glucose, polyethylene glycol-400, EDTA-2Na, and sodium stearate, and the added amount of the surfactant is 0.1%-0.5% of the mass of the mixed solvent.
[0020] In some embodiments, the mass ratio of the added amount of the sodium ion battery layered positive electrode material to the solvent in S2 is 1:1-2.
[0021] In some embodiments, the calcination process conditions in S4 are: temperature 300° C.-900° C., time 2 h-12 h.
[0022] The present invention discloses a method for preparing a sodium ion battery layered positive electrode material coated with a fluoroboric acid composite, wherein a sodium ion battery layered positive electrode material is coated with a simple and controllable thin layer by a fluoroborate, and a composite coating system of a fluoride and a borate is generated on the surface of the material, and the coating is carried out by a liquid phase method, which can penetrate into the polycrystalline sphere of the sodium ion battery layered positive electrode material, and an inorganic thin layer coating layer is generated on the surface of each primary particle, which can significantly improve the air stability of the material, and can also promote the generation of a CEI film during the charge and discharge process, improve the oxidation resistance stability of the positive electrode material under high voltage, inhibit a series of side reactions of the positive electrode, and protect the structural stability of the positive electrode material under high voltage, so as to achieve the purpose of improving the electrochemical performance of the material. The present invention is simple to operate, has mild conditions, and has a controllable process, can be industrialized on a large scale, and has good application prospects. It can be understood that the beneficial effects of the second aspect mentioned above can be referred to the relevant description in the content of the first aspect mentioned above, and will not be repeated here. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0024] Figure 11 is an XRD diagram of the fluoroborate-coated sodium ion battery positive electrode material prepared in Example 1 of the present invention and Comparative Example 1;
[0025] Figure 2 is a SEM image of the fluoroborate-coated sodium ion battery positive electrode material prepared in Example 1 of the present invention;
[0026] Figure 3 This is an XPS graph of the sodium ion battery positive electrode material coated with fluoroborate prepared in Example 1 of the present invention;
[0027] Figure 4 This is a TEM image of the sodium ion battery positive electrode material coated with fluoroborate prepared in Example 1 of the present invention;
[0028] Figure 5 This is an EDS image of the sodium ion battery positive electrode material coated with fluoroborate prepared in Example 1 of the present invention;
[0029] Figure 6 This is a test diagram of the cycle performance of Example 1 of the present invention and Comparative Example 1 at room temperature 25°C;
[0030] Figure 7 It is a cycle performance diagram of a battery assembled with the positive electrode materials of Comparative Example 1 and Example 1 of the present invention after 100 cycles at a rate of 1C (1C=120 mA / g). DETAILED DESCRIPTION
[0031] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present application more clearly understood, the present application is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.
[0032] In this application, the term "and / or" describes the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone. A and B can be singular or plural. The character " / " generally indicates that the associated objects are in an "or" relationship.
[0033] In the present application, "at least one" means one or more, and "more than one" means two or more. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single or plural items. For example, "at least one of a, b, or c", or "at least one of a, b, and c", can all mean: a, b, c, a~b (i.e. a and b), a~c, b~c, or a~b~c, where a, b, c can be single or multiple, respectively.
[0034] The terms "first" and "second" are used only for descriptive purposes to distinguish objects such as substances from each other, and should not be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated. For example, without departing from the scope of the implementation regulations of this application, the first XX may also be referred to as the second XX, and similarly, the second XX may also be referred to as the first XX. Therefore, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features.
[0035] The terms used in the embodiments of the present application are only for the purpose of describing specific implementation rules, and are not intended to limit the present application. The singular forms "a", "said" and "the" used in the implementation rules of the present application and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.
[0036] It should be understood that in the various embodiments of the present application, the size of the serial number of each process does not mean the order of execution, some or all of the steps can be executed in parallel or sequentially, and the execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the implementation regulations of this application.
[0037] The weight of the relevant components mentioned in the embodiment description of the present application can not only refer to the specific content of each component, but also represent the proportional relationship between the weights of the components. Therefore, as long as the content of the relevant components is proportionally enlarged or reduced according to the embodiment description of the present application, it is within the scope disclosed in the embodiment description of the present application. Specifically, the mass described in the embodiment description of the present application can be a mass unit known in the chemical industry such as μg, mg, g, kg, etc.
[0038] Unless otherwise defined, all professional terms used below have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.
[0039] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in this application can be purchased from the market or prepared by existing methods.
[0040] The technical solution of the present application is illustrated below through specific embodiments and comparative examples.
[0041] In order to enable the above implementation details and operations of the present application to be clearly understood by those skilled in the art, and to significantly demonstrate the improved performance of the embodiments of the present application, the above technical solutions are illustrated by means of multiple embodiments below.
[0042] Embodiment 1:
[0043] A method for preparing a sodium ion battery layered positive electrode material coated with fluoroboric acid composite comprises the following steps:
[0044] (1) dissolving stoichiometric amounts of H4BF4N and EDTA-2Na in 200 ml of water and ethanol (water:ethanol=3:1), stirring to obtain a clear ammonium fluoroborate solution A with a concentration of 0.05 mol / L;
[0045] (2) Under continuous stirring at room temperature, the positive electrode active material NaNi 0.33 Fe 0.33 Mn 0.33 O2 was gradually added to solution A, and stirring was continued for 5 min after the addition was completed;
[0046] (3) The turbid liquid after the reaction in step (2) is centrifuged and washed, and then placed in a vacuum drying oven at 80° C. for 12 h to obtain a sodium ion battery layered positive electrode material with fluoroborate uniformly attached to the surface, named NaNi 0.33 Fe 0.33 Mn 0.33 O2-FB-1.
[0047] (4) In a compressed air atmosphere, the material obtained in step (3) was heated to 300° C. at a heating rate of 3° C. / min and kept warm for 2 h, and then further heated to 550° C. for 1 h and then cooled to room temperature to obtain a sodium ion battery layered positive electrode material uniformly coated with F and B elements on the surface of the present invention, named NaNi 0.33 Fe 0.33 Mn 0.33 O2@FB-1.
[0048] Embodiment 2:
[0049] A method for preparing a sodium ion battery layered positive electrode material coated with fluoroboric acid composite comprises the following steps:
[0050] The surfactant in the above Example 1 is adjusted to a stoichiometric amount of polyethylene glycol-400, and the solvent is methanol:ethylene glycol = 1:1. The rest is the same as in Example 1, and the sodium ion battery layered positive electrode material with F and B elements uniformly coated on the surface of the present invention is obtained, which is named NaNi 0.33 Fe 0.33 Mn 0.33 O2@FB-2.
[0051] Embodiment 3:
[0052] A method for preparing a sodium ion battery layered positive electrode material coated with fluoroboric acid composite comprises the following steps:
[0053] The difference between this embodiment and embodiment 1 is that no surfactant sodium stearate is added. The surfactant in embodiment 1 is adjusted to the stoichiometric sodium stearate, the solvent is ethylene glycol:DMF=6:1, the coating agent is Sn(BF4)2, and the positive electrode active material material is Na 0.8 Ni 0.233 Fe 0.333 Mn 0.333 Ca 0.01 Cu 0.05 Zn 0.04 O2, low temperature sintering system: 3℃ / min
[0054] The heating rate was raised to 300°C and kept for 2h, and then the temperature was raised to 450°C for 1h and then cooled to room temperature. The rest was the same as in Example 1. The sodium ion battery layered positive electrode material with Sn, F and B elements uniformly coated on the surface of the present invention was obtained, named NaNi 0.33 Fe 0.33 Mn 0.33 O2@Sn-FB.
[0055] Embodiment 4:
[0056] A method for preparing a sodium ion battery layered positive electrode material coated with fluoroboric acid composite comprises the following steps:
[0057] The surfactant in the above Example 1 is adjusted to the stoichiometric glucose, the solvent is ethanol:DMF=4:1, the coating agent is Ca(BF4)2, and the positive electrode active material is
[0058] Na 0.6 Mn 0.4 Cu 0.1 Fe 0.25 Ni 0.1 Al 0.05 Mg 0.05 Sn 0.05 O2, low temperature sintering system: heating up to 250℃ at a rate of 3℃ / min and keeping it for 2h, further heating up to 500℃ for 3h and cooling to room temperature, the rest is the same as Example 1. That is, the sodium ion battery layered positive electrode material with Ca, F and B elements uniformly coated on the surface of the present invention is obtained, named NaNi 0.33 Fe 0.33 Mn 0.33 O2@Ca-FB.
[0059] Comparative Example 1:
[0060] Comparative Example 1 is a base positive electrode active material NaNi 0.33 Fe 0.33 Mn 0.33O2 was used for electrochemical assembly and electrochemical performance testing.
[0061] Comparative Example 2:
[0062] A method for preparing a sodium ion battery layered positive electrode material coated with fluoroboric acid composite comprises the following steps:
[0063] (1) The stoichiometric H4BF4N and the positive electrode active material NaNi 0.33 Fe 0.33 Mn 0.33 O2 was placed in a ball mill jar and ball milled at 300 rpm for 2 h. The obtained material was used for the next experiment.
[0064] (2) Under a compressed air atmosphere, the material obtained in step (3) was heated to 300°C at a heating rate of 3°C / min and kept at this temperature for 2 h, and then further heated to 550°C for a second time and kept at this temperature for 1 h before cooling to room temperature to obtain a final material coated by the solid phase method.
[0065] Comparative Example 3:
[0066] A method for preparing a layered positive electrode material for a sodium ion battery comprises the following steps:
[0067] The stoichiometric amount of polyethylene glycol-400 was dissolved in 200 ml of (methanol:ethylene glycol = 1:1) without adding the coating agent fluoroboric acid, and stirred to obtain a clear solution A; the positive electrode active material NaNi 0.33 Fe 0.33 Mn 0.33 O2 was gradually added to solution A, and stirring was continued for 5 min after the addition was completed; the turbid liquid after the reaction was completed was centrifuged and washed, and then placed in a vacuum drying oven at 80°C for 12 h. Under a compressed air atmosphere, the obtained material was heated to 300°C at a heating rate of 3°C / min and kept warm for 2 h, and then further heated to 550°C for a second time and kept warm for 1 h before cooling to room temperature.
[0068] Comparative Example 4:
[0069] A method for preparing a layered positive electrode material for a sodium ion battery comprises the following steps:
[0070] The stoichiometric amount of Sn(BF4)2 was dissolved in 200 ml of a solution containing ethylene glycol:DMF=6:1, and stirred to obtain a clear solution A without adding a surfactant, sodium stearate; the positive electrode active material Na 0.8 Ni 0.233 Fe 0.333 Mn 0.333 Ca 0.01 Cu 0.05Zn 0.04 O2 was gradually added to solution A, and stirring was continued for 5 minutes after the addition was completed; the turbid liquid after the reaction was completed was centrifuged and washed, and then placed in a vacuum drying oven at 80°C for 12 hours. In a compressed air atmosphere, the obtained material was heated to 300°C at a heating rate of 3°C / min and kept warm for 2 hours, and then further heated to 450°C for a second time and kept warm for 1 hour before cooling to room temperature.
[0071] Comparative Example 5:
[0072] A method for preparing a layered positive electrode material for a sodium ion battery comprises the following steps:
[0073] The stoichiometric amount of Ca(BF4)2 was dissolved in 200 ml of a solution containing ethanol:DMF=4:1, and the solution was stirred to obtain a clear solution A. The surfactant glucose was added. Under continuous stirring at room temperature, the positive electrode active material LiNi 0.6 Mn 0.2 Co 0.2 O2 was gradually added to solution A, and stirring was continued for 5 minutes after the addition was completed; the turbid liquid after the reaction was completed was centrifuged and washed, and then placed in a vacuum drying oven at 80°C for 12 hours. In a compressed air atmosphere, the obtained material was heated to 250°C at a heating rate of 3°C / min and kept warm for 2 hours, and then further heated to 500°C for a second time and kept warm for 3 hours before cooling to room temperature. The lithium ion battery layered positive electrode material with Ca, F and B elements uniformly coated on the surface of the present invention was obtained, named LiNi 0.6 Mn 0.2 Co 0.2 O2@Ca-FB.
[0074]
[0075]
[0076] Test example:
[0077] 1. Characterization of the structure and morphology of materials.
[0078] from Figure 1 From the XRD diagram, it can be seen that the aqueous liquid phase coating and the high-temperature sintering surface trace F and B element coating do not destroy the crystal structure of the raw material itself; Figure 2 From the SEM analysis, it can be seen that the surface morphology of the material does not change significantly during the aqueous liquid phase coating process and high-temperature sintering. Figure 3 It can be seen from the XPS that there are F and B with a valence state of -1 in the bulk phase of the material; Figure 4From the TEM image analysis, it can be seen that this method can achieve uniform surface coating of F and B complex layers; and it can be seen that the crystal structure of the material does not change significantly after the addition of F and B elements to the surface of the aqueous liquid phase; Figure 5 From the EDS graph, we can see that the F and B elements are evenly distributed on the surface of the particles, indicating that this method achieves uniform coating of transition metal elements on the surface of the electrode material.
[0079] 2. Battery assembly and electrochemical performance testing.
[0080] The prepared positive electrode material was mixed with a binder polyvinylidene fluoride (PVDF) and a conductive agent Super-P in a mass ratio of 8:1:1, and an appropriate amount of solvent N-methylpyrrolidone (NMP) was added to prepare a slurry. The slurry was evenly coated on the aluminum foil with an aluminum foil as a current collector and dried in vacuum at 100 °C for 12 h to obtain NaNi 0.33 Fe 0.33 Mn 0.33 O2@FB-2 composite cathode. Subsequently, the prepared composite cathode, separator, electrolyte (1 mol L -1 NaClO4 / PC+FEC (95:5)), sodium metal negative electrode (sodium block with a purity of 99.5%, the surface oxide layer was cut off in a glove box, rolled into thin sheets, and the metal sodium was cut into round sodium sheets with a 12mm diameter round punch), positive electrode shell and negative electrode shell were assembled into button-type sodium ion batteries. Finally, the battery was tested for constant current charge and discharge at 25°C and a voltage range of 2-4V. The test results of Example 1 and Comparative Example 1 were as follows: Figure 6 shown. Figure 7 The cycle performance diagram of the battery assembled with the positive electrode materials of Comparative Example 1 and Example 1 of the present invention after 100 cycles at a rate of 1C (1C=120 mA / g) shows that the sodium ion battery layered positive electrode material with F and B elements uniformly coated on the surface can significantly improve the cycle stability of the battery.
[0081] In the above embodiments, the description of each embodiment has its own emphasis. For parts that are not described or recorded in detail in a certain embodiment, reference can be made to the relevant descriptions of other embodiments.
[0082] The embodiments described above are only used to illustrate the technical solutions of the present application, rather than to limit them. Although the present application has been described in detail with reference to the aforementioned embodiments, a person skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. Such modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present application, and should all be included in the protection scope of the present application.
Claims
1. A sodium ion battery layered positive electrode material coated with fluoroboric acid, characterized in that: The general formula is Na x TMO2, wherein 0.44≤x≤1.0, the surface of the sodium ion battery layered positive electrode material has a composite coating layer of fluoride and borate, and the surface of the primary particles constituting the sodium ion battery layered positive electrode material has an inorganic coating layer.
2. The sodium ion battery layered positive electrode material according to claim 1, characterized in that The TM is one or a combination of transition metal ions Ti, Mg, Co, Cu, Al, Zn, Li, Ni, Fe, Mn and Zr; the thickness of the composite coating layer is 5-10 nm.
3. A method for preparing a sodium ion battery layered positive electrode material coated with fluoroboric acid as claimed in claim 1, characterized in that: The following steps are involved: S1, preparing a mixed solvent of water and a polar organic solvent, adding fluoroborate and a surfactant, and mixing them uniformly to obtain a first solution; S2, adding a sodium ion battery layered cathode material to the first solution and stirring to obtain a second suspension; S3, stirring the second suspension, centrifuging and drying to obtain a first sodium ion battery layered positive electrode material with fluoroborate uniformly attached to the surface; S4, calcining the first sodium ion battery layered positive electrode material to obtain the sodium ion battery layered positive electrode material coated with fluoroboric acid.
4. The preparation method according to claim 3, characterized in that: In the mixed solvent described in S1, the volume ratio of water is greater than or equal to 50%, and the polar organic solvent is a combination of one or more of ethanol, methanol, ethylene glycol, glycerol or DMF.
5. The preparation method according to claim 3, characterized in that: The fluoroborate in S1 is a combination of one or more of sodium fluoroborate, ammonium fluoroborate, stannous fluoroborate or lithium fluoroborate, and the amount of the fluoroborate added is 0.5%-5% of the mass of the mixed solvent.
6. The preparation method according to claim 3, characterized in that: The surfactant in S1 is a combination of one or more of glucose, polyethylene glycol-400, EDTA-2Na, and sodium stearate, and the added amount of the surfactant is 0.1%-0.5% of the mass of the mixed solvent.
7. The preparation method according to claim 3, characterized in that: The mass ratio of the added amount of the sodium ion battery layered positive electrode material to the solvent in S2 is 1:1-2.
8. The preparation method according to claim 3, characterized in that: The calcination process conditions in S4 are: temperature 300°C-900°C, time 2h-12h.
Citation Information
Patent Citations
Coating and modifying method for electrode material of lithium ion battery
CN105932236A
Surface treatment modified lithium-rich manganese-based layered cathode material and preparation method
CN106410135A
Element-uniformly-coated ternary lithium ion battery positive electrode material and preparation method thereof
CN114695873A
Method for preparing layered positive electrode material of sodium ion battery and sodium ion positive electrode material
CN115872463A
Preparation method of high-nickel ternary positive electrode material and method for preparing button cell
CN117727884A